Fortymile caribou herd range isopleths, occurrence distributions, and associated vegetation change data, Alaska and Yukon Territory (1991 - 2021) ... - Orndahl, Kathleen; Bentzen, Torsten; Macander, Matthew; Palm, Eric (Arctic Data Center, 2025)
We assessed the range characteristics of the Fortymile migratory caribou (Rangifer tarandus) herd in east-central Alaska and west-central Yukon Territory as it grew (1992-2017) then declined (2017-2020) to analyze whether range size, location and density changed over this time period. In addition, we assessed the correlation between caribou density and vegetation change over this time period using remotely sensed estimates of plant functional type fractional cover. This dataset provides: a) the Fortymile range isopleth data used to assess changes in range characteristics, b) the Forytmile range occurrence distributions used to analyze spatial patterns in caribou relative spatial density, and c) summarized vegetation change data associated with caribou relative spatial density classes. ...